Optimization of Environmental and Defense of the New Capital City ‘Nusantara’ Based on Pancasila and SDGs - Xavier Nugraha; Krisna Angela; Natasha Caecilia Lisanggraeni Rositaputri; Amilah Fadhlina (Journal of Judicial Review, 2022)
The development and industrialization of the new capital city "Nusantara" which aims to realize equitable development, has an impact on reducing forest and marine sustainability, related to environmental rights and rights to the environment as mandated in Article 28H of The 1945 Constitution. In addition, this development also threatens national defense because the archipelago is adjacent to international borders, thus triggering territorial disputes between countries. The research uses normative legal research methods with the statute and conceptual approach. This research purposed to analyze the preservation of forests and seas, security, and defense as a result of the development and industrialization of the new capital city "Nusantara" based on the Sustainable Development Goals (SDGs). The result showed that implementing the development and automation of the new capital city "Nusantara" must pay attention to the values of Pancasila and the 1945 Constitution. In addition, the management and conservation of forests and seas need to refer to the 15th SDGs goal and the 16th SDG related to defense. and national security.